Incremental prognostic value of global longitudinal strain in patients with type 2 diabetes mellitus. Issue 1 (December 2016) - Liu, Ju-Hua; Chen, Yan; Yuen, Michele; Zhen, Zhe; Chan, Carmen; Lam, Karen; Tse, Hung-Fat; Yiu, Kai-Hang
Abstract Background Patients with type 2 diabetes mellitus (T2DM) are at high risk for cardiovascular events. The aim of the study was to assess whether global longitudinal strain (GLS) provides prognostic value in these patients. Methods A total of 247 T2DM patients without history of cardiovascular complications and participated in the CDATS study were prospectively enrolled. Left ventricular (LV) systolic function was assessed by LV ejection fraction and speckle tracking derived LV systolic GLS. Diastolic function was assessed by E/E′ ratio defined as the passive trans-mitral LV inflow velocity to tissue Doppler imaging velocity of the medial mitral annulus. Cardiovascular event included acute coronary syndrome, cerebrovascular stroke, hospitalization for heart failure and cardiovascular death. Results A total of 18 cardiovascular events occurred during a median follow-up duration of 33 months. Both E/E′ ratio [hazard ratio (HR) 1.15, P < 0.01] and GLS (HR 1.39, P < 0.01) were independently associated with cardiovascular events. Importantly, GLS provided incremental prognostic information in addition to clinical data, HbA1c and E/E′ ratio (Chi square 77.46, P = 0.04). Receiver-operator characteristic curve analysis demonstrated that E/E′ ratio [area under curve (AUC) 0.66, P = 0.03] and GLS (AUC 0.72, P < 0.01) were strong predictors of cardiovascular events. Kaplan–Meier analysis showed that patients with E/E′ > 13.6 or GLS > −17.9 % were associated with cardiovascular events. The presence of either a high E/E′ ratio or an impaired GLS provides an excellent negative predictive value of cardiovascular events in these patients. Conclusions In T2DM patients with no history of cardiovascular disease, impaired GLS was associated with cardiovascular events and provided incremental prognostic value.